Analysis of Birth Certificate Issuance Services at the Medan City Population and Civil Registration Service - Fahmi Rizky; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2022)
A Civil Registry document which explains the child's name, gender, parents' names, and citizenship status recorded as a result of a birth is called a Birth Certificate. This research process uses a descriptive qualitative method whose purpose is to describe the data analysis and make it into a narrative form with data collection techniques through direct observation and interviews with the community. The Department of Population and Civil Registration in Medan City is a public service agency that really helps the community in managing Birth Certificates. The process for making a birth certificate is sufficient in accordance with the SOP. In terms of public services provided, it also provides solutions to simplify and speed up the administrative process by making online access called SIBISA and greatly facilitates the management of Birth Certificates during the current pandemic.